Optimal consensus for uncertain high‐order multi‐agent systems by output feedback - Tang, Yutao; Zhu, Kui (International journal of robust and nonlinear control, 2022)
The distributed optimal output consensus problem for high‐order multi‐agent systems has been studied recently. In this article, we further focus on the same problem for high‐order multi‐agent systems subject to parametric uncertainties and aim at distributed robust controllers by measurement output feedback. We first develop a dynamic compensator to estimate the expected optimal consensus point and convert the problem into several decentralized robust tracking problems. Then, by combining the integral control technique and dirty derivative observer technique, we constructively propose a distributed output feedback integral controller to solve this problem under a mild graph connectivity condition.